Replacement model for higher education institution hostel building maintenance in Malaysia - Yuseni, Ab Wahab; Hasan Basari, Abd Samad; Hussin, Burairah (2014)
This paper is part of an ongoing research on the development of maintenance management cost model for Higher Education Institution Hostel Building in Malaysia where the case study is conducted at Kolej Universiti Islam Melaka (KUIM). The model is developed to analyze the total cost curve for various values of the uncertain parameter, and noting the effect of this variation on the optimal solution. The decision areas addressed based on the replacement action that are assumed to be known with certainty. This is due to the item is not subject to failure but consider the operating cost with use. The study is aimed to assist engineers in deciding an appropriate replacement policy. This is usually useful to plot the total cost per unit time curve. The advantage of the curve is that, along with giving the optimal value, it shows the total cost around the optimum.